2021
DOI: 10.1016/j.chest.2021.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Giant Intrathoracic Mass in a Young Woman With Acute Kidney Injury

Abstract: A 35-year-old woman without past medical history sought treatment for fatigue and dry cough of 3 weeks' duration. Basic laboratory tests revealed severe anemia. She had no history of bleeding, hemoptysis, dyspnea, or fever. The patient was admitted for RBC transfusion and more extensive diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…92 In contrast, lipofibroadenoma can cause autoimmune disorders while few immature T cells accompany the cord-like thymic epithelium. 93 This supports the idea that the presence of immature T cells alone is insufficient for developing TAMG, but rather the nature of neoplastic epithelial cells and/or tumor microenvironment is involved in the pathogenesis.…”
Section: Disease-relevant Phenotypes In Tetssupporting
confidence: 75%
“…92 In contrast, lipofibroadenoma can cause autoimmune disorders while few immature T cells accompany the cord-like thymic epithelium. 93 This supports the idea that the presence of immature T cells alone is insufficient for developing TAMG, but rather the nature of neoplastic epithelial cells and/or tumor microenvironment is involved in the pathogenesis.…”
Section: Disease-relevant Phenotypes In Tetssupporting
confidence: 75%
“…In the case presented here we did not identify genetic aberrations, specifically no HMGA -2 mutation was found, as described recently in thymolipoma, nor were CNVs documented. In a single recently described LFA case no fusion transcripts were detected ( 13 ), taken together with our case, there are currently no features which support a neoplastic process.…”
Section: Discussionsupporting
confidence: 40%
“…The follow-up of all reported cases after surgical removal of the LFA is favorable, no recurrences have been reported and patients made a good recovery. While the patient described in the report by Matyjek and co-workers made an initial good recovery from the operative procedure to remove a large LFA, she did suffer progressive anti neutrophil cytoplasmic antibody (ANCA)-vasculitis associated renal failure ( 13 ). Although it was suggested that the vasculitis may have been associated with the LFA given the co-occurrence of two rare diseases, this may be contested as the ANCA-associated vasculitis progressed after removal of the LFA.…”
Section: Discussionmentioning
confidence: 99%